Impact of the internet of things on 3rd cycle students motivation in an interdisciplinary approach to science - Magalhães, Andreia (2020)
Recognizing in Iot an advantage to make teaching evolve to a model based on the development of competences, which requires students to play a more active role, it is intended, using a mixed methodology, to study its impact on 3rd cycle student motivation, in an interdisciplinary approach to science. Thus, through surveys, student questionnaires and focus group interviews with teachers, the obtained data show that students, in general, remain motivated. This brings numerous benefits to its development, leading to greater autonomy in the acquisition of knowledge.